Electrosynthesis of anisotropic biogenic silver nanoparticles as a promising antibacterial agent using Stachytarpheta jamaicensis leaf extract - Hermanto, Dhony; Ismillayli, Nurul; Wiranatasari, Thiffany A. L.; Mudasir, Mudasir; Siswanta, Dwi; Kuswandi, Bambang; Siswoyo, iswoyo; Suprapto, Suprapto; Prasetyoko, Didik (Penerbit Universiti Kebangsaan Malaysia, 2024)
Antibiotic-resistant bacteria provide a great opportunity to use silver nanoparticles (AgNPs) as potential antibiotic replacements. This work utilized Stachytarpheta jamaicensis leaf extract (SJLE)-mediated electrosynthesis of biogenic AgNPs. By using two silver rods and SJLE as the electrolysis medium, biogenic AgNP is produced through electrosynthesis. The properties of the formed AgNPs and SJLE phytochemical composition were examined. The disc diffusion method was utilized to evaluate AgNPs’ antibacterial efficacy against Escherichia coli and Staphylococcus aureus. The high amount of phenolics, flavonoids, and tannins in SLJE provides biomolecules rich in -OH and carbonyl groups, allowing SLJE to have antimicrobial effects as well as act as a capping agent and bioreductor during electrosynthesis. The presence of functional groups from various phytochemicals leads to the formation of anisotropic AgNP crystals with a size of 38.22 ± 13.06 nm and high purity (95.75 ± 0.43%). Antibacterial activity tests against E. coli and S. aureus show that anisotropic biogenic AgNPs outperformed spherical AgNPs, probably due to the angular AgNPs’ ease of penetration into bacterial cell walls. The characteristics of the AgNPs developed induced outstanding antibacterial efficacy against E. coli and S. aureus. Thus, SLJE-based electrosynthesis provides a synergistic synthetic design of AgNPs as antibacterial agents with several potential long-term advantages, including high purity, fast synthesis, low cost, absence of hazardous ingredients, and simplicity in scaling up.